New p-terphenyls from the endophytic fungus Aspergillus sp. YXf3. Issue 1 (1st January 2017) - Yan, Wei; Wuringege,; Li, Sui-Jun; Guo, Zhi-Kai; Zhang, Wen-Jing; Wei, Wei; Tan, Ren-Xiang; Jiao, Rui-Hua
Graphical abstract: Abstract: Five new p -terphenyls named prenylterphenyllin D (1 ), prenylterphenyllin E (2 ), 2′- O -methylprenylterphenyllin (3 ), 4- O -methylprenylterphenyllin (4 ) and 3′- O -methylterphenyllin (5 ) together with seven known compounds (6 –12 ), were isolated from cultures of Aspergillus sp. YXf3. The structures of the new compounds were elucidated by extensive MS and NMR analyses. The NMR and MS data of5 is reported for the first time, as its structure was listed in SciFinder Scholar with no associated reference. Compounds6 and7 were distinguished from each other on the basis of 2D NMR experiments. Compounds1, 2, 3 and8 showed antibacterial activities against X. oryzae pv. oryzicola Swings and E. amylovora with the same MIC values of 20 μg/mL while10 exhibited activities against E. amylovora with an MIC value of 10 μg/mL.